Topically Applied Resiquimod versus Imiquimod as a Potential Adjuvant in Melanoma Treatment - Supreeda Tambunlertchai; Sean M. Geary; Aliasger K. Salem (MDPI AG, 2022)
Melanoma is the most lethal form of skin cancer and surgery remains the preferred and most effective treatment. Nevertheless, there are cases where surgery is not a viable method and alternative treatments are therefore adopted. One such treatment that has been tested is topical 5% imiquimod (IMQ) cream, which, although showing promise as a treatment for melanoma, has been found to have undesirable off-target effects. Resiquimod (RSQ) is an immunomodulatory molecule that can activate immune responses by binding to Toll-like receptors (TLR) 7 and 8 and may be more effective than IMQ in the context of melanoma treatment. RSQ can cross the stratum corneum (SC) easily without requiring pretreatment of the skin. In a gel formulation, RSQ has been studied as a monotherapy and adjuvant for melanoma treatment in pre-clinical studies and as an adjuvant in clinical settings. Although side effects of RSQ in gel formulation were also reported, they were never severe enough for the treatment to be suspended. In this review, we discuss the potential use of RSQ as an adjuvant for melanoma treatment.